PELAKSANAAN PROJEK SUMBANG DUO BALEH PADA DIMENSI BERIMAN, BERTAKWA KEPADA TUHAN YANG MAHA ESA, DAN BERAKHLAK MULIA DI MTsN 2 KOTA PARIAMAN - Annisa Indriani; Khadijah; Rilci Kurnia Illahi; Duski Samad; Aziza Meria (ADIBA : JOURNAL OF EDUCATION, 2025)
This thesis was motivated by the discovery of impolite behavior among students, such as not greeting teachers when passing by them, as well as many students eating and drinking while walking or standing. This condition became a serious concern, considering that the madrasah was expected to instill values of politeness and other moral behaviors. In addition, the "Sumbang Duo Baleh Project," which was said to be a solution to this student behavior phenomenon, had not yet shown the expected results, as student behavior remained unchanged even after two meetings. This issue was important to study in order to understand how the program worked, the challenges faced during its implementation, and to what extent it was effective. The aim of this research was to explore the planning, implementation, and evaluation of the Sumbang Duo Baleh Project and its impact on student character at MTsN 2 Kota Pariaman. This study used a qualitative approach with a case study method. Data sources were obtained from the head of the madrasah, curriculum deputy, project coordinator, project supervising teachers, students, modules, and activity documentation.The results of the study showed, first, that the planning of the Sumbang Duo Baleh Project began with considering the madrasah’s readiness to implement the Merdeka Curriculum. Then, the project planning process included designing modules and organizing the project team and their responsibilities. Second, the implementation of the Sumbang Duo Baleh Project activities took place both inside and outside the classroom, consisting of material delivery by teachers, talent performances, and drama presentations about Sumbang Duo Baleh. During implementation, several challenges and obstacles were encountered, such as teachers being challenged to explore relevant materials suitable to students' developmental stages, weather disturbances during outdoor activities, and schedule conflicts with grade IX classes, which caused technical issues like the use of sound systems. Third, the assessment in the Sumbang Duo Baleh Project was limited to the evaluation of the students’ drama performances and attitude assessments, which were carried out by observing students’ behavior both during and outside the project activities. Fourth, although after two meetings the students' behavior was still lacking in politeness, the implementation of the Sumbang Duo Baleh Project eventually had a positive impact on the improvement of student behavior. They became more aware of manners based on Minangkabau customs, showed greater respect for teachers and parents, and demonstrated more polite behavior in speech and dress.